Student Analysis of Violence in The Antares Series Season 2 - Felani, Alfian Nur Fauzan Wahyu; Aisyah, Vinisa Nurul (Universitas Muhammadiyah Surakarta, 2023)
This study has the aim of finding out how the reception of meaning by the audience regarding violence is contained in the Web Series Antares 2 which premiered on WeTV video streaming media. The study used Stuart Hall's reception theory. Methods in This study used qualitative methods with data retrieval using interview techniques. The results of this study showed that 2 informants were in the dominant position, two informants were in the negotiating position and 2 informants in the opposition position. The informant is in a dominant position because the informant has the same environmental background and experience as the Web Series Antares 2. The informant is in a negotiating and oppositional position because the informant has a different gender and environmental background.